DIRECTED READING ACTIVITY (DRA) APPLICATION IN ENGLISH READING COMPREHENSION CLASSROOM - Imam Munandar; Srimurni (Jurnal As-Salam, 2021)
This research manages to analyze the effectiveness of  DRA in enhancing students ‘skill in reading comprehension. The researchers carried out the research at SMP N 4 Takengon, in which they found that teachers faced some problems in teaching reading comprehension to students. To figure out the answer, the research applies quantitative research with experimental approach. After statistically obtaining and interpreting the data, the study concludes that Directed Reading Activity (DRA) method is able to increase students reading comprehension skill. This is because that Directed Reading Activity (DRA) is a teacher strategy in reading comprehension that emphasizes on instructional support before, during, and aftermath the reading. Meanwhile, the research found that this strategy is also able to increase and build stronger student vocabulary and reading skill. In conclusion, the DRA strategy is effective in improving students’ ability in reading comprehension, and also building their vocabulary.